Study of the mineral composition of some soils of the Syrian island - Sulaiman, Hussein Sulaiman; Abd Alrazaq, Omar; Kaba, Rami (Journal of agricultural, environmental and veterinary sciences, 2020)
The study was carried out with the aim of determining the mineral composition of the soil from the north-eastern region in Al-Hasakah governorate in Syria and its effect on some physical and chemical soil properties. Where five sections were excavated and three samples of dirt were taken from each section according to horizons, The results of the mineral composition study showed a group of primary metals and the highest percentage of calcite in the studied soils, Followed by quartz metal in terms of spread in the studied soils, but the potassium feldspar (Othoclaz) was less than calcite and quartz in the studied soils, while found only pyroxene in the soil of the fourth and fifth sectors where the rock basalt mother, while found Baligorskit metal and a small percentage in all types The clay minerals were found to be high in the fourth sector and less on the horizon A1 for the other sectors. There was no A0 in the horizon for the first two sectors (Al-Hasakah) and the second (Qamishli). Mica (often alkaline), kaolinite and chlorite were found to be lower in thickness than in all soil samples studied. The results of the physical study showed that most of the soils have a clay texture, with the lowest percentage of mud and hysteroscopic in the surface depth of Qamishli soil (Tal Maarouf) (41.00) and (5.06)%, respectively, in Tin Tin and Shakhala, in the third depth of the Malikiyah soil (Deir Tigris), and the bulk density values ​​ranged between (1.19-1.33) g / cm3, and the real density values ​​ranged from (2.62-2.75) g / cm3, and was accompanied by a variation in the values ​​of the total porosity, as its value ranged between (50.15–54.58)%. The chemical and fertility results showed that the degree of (pH) soil is moderate on the surface horizon of al-kamshli soil, reaching (7.71), and the average alkalinity becomes slightly more than (8.00), and the soil content of the exchanged cations ranged from medium to high, ranging between (32.24 and 45.32). m.m / 100g soil, and the calcium cation occupies the first place on the adsorption complex, followed by magnesium. The content of the studied soils from the organic matter in the first depth is considered low because its value ranges between (00.5 - 01.0)%. The total calcium carbonate percentage ranged between the lowest value (21.63%) in the Al-Malikiyah soil (Deir Djla), and the highest value (31.91%) in Qamishli (Tal Maouf). By studying the kinetics of potassium, it was found that the ARKe values ranged between (0.0092 and 0.183) (mol / liter) 1/2, where the highest value of ionic activity was recorded in Malikiyah soil (0.0183) (mol / liter) 1/2 and the lowest value of ionic activity was recorded in Qamishli soil. 0.0092 (mol / liter) 1/2. The values of K∆ for the studied soils ranged from (0.3595 - 0.885) centimole. Kg-1, where the values of the potassium voltage regulation values of the studied soils ranged between (33.751- 60.314) [cmol kg-1] / (M L-1) 0. 5]. That the values of the Capon modulus ranged between (0.867 - 1.713) liters to mol -1.